Implementation of the principles of primary health care in a rural area of South Africa - Surona Visagie; Marguerite Schneider (AOSIS, 2014)
Background: The philosophy of primary healthcare forms the basis of South Africa's health policy and provides guidance for healthcare service delivery in South Africa. Healthcare service provision in South Africa has shown improvement in the past five years. However, it is uncertain as to whether the changes have reached rural areas and if primary healthcare is implemented successfully in these areas. Objectives: The aim of this article is to explore the extent to which the principles of primary healthcare are implemented in a remote, rural setting in South Africa. Method: A descriptive, qualitative design was implemented. Data were collected through interviews and case studies with 36 purposively-sampled participants, then analysed through Interpretative Phenomenological Analysis. Results: Findings indicated challenges with regard to client-centred care, provision of health promotion and rehabilitation, the way care was organised, the role of the doctor, healthworker attitudes, referral services and the management of complex conditions. Conclusion: The principles of primary healthcare were not implemented successfully. The community was not involved in healthcare management, nor were users involved in their personal health management. The initiation of a community-health forum is recommended. Service providers, users and the community should identify and address the determinants of ill health in the community. Other recommendations include the training of service managers in the logistical management of ensuring a constant supply of drugs, using a Kombi-type vehicle to provide user transport for routine visits to secondary- and tertiary healthcareservices and increasing the doctors' hours.